Coupling Efficiency of a Spot Size Converter for Optical Fiber-Chip Connections - Wildan Panji Tresna; Dedi Riana; Reza Rendian Septiawan (Diponegoro University Semarang Indonesia, 2023)
The light propagation in optical waveguide must be able to maintain low propagation loss, low coupling loss and scattering loss condition, especially in the junction. In this research, a spot size converter is proposed to preserve the lowest coupling loss. This optical converter is composed of a single mode optical fiber (SiO2) including inversed taper. The optical input signal from the optical fiber is launched into photonic integrated circuits and then coupled into the Si-Slab waveguide. Furthermore, linear form with the length dependence has been studied to obtain the optimal position of optical fiber and the chip and analyzed the coupling efficiency of it. The purpose of this research is to procure the optimal form of spot size converter. The simulation result shows the coupling loss of linear form is 0.62 dB and 0.24 dB on TE and TM mode condition respectively. Along with the increase in the taper length, the coupling loss obtained tends to decrease as well. So that, it can be assumed the design of a linear form with 100 μm taper length provides the highest coupling efficie ncy.